Disinfection applications of ozone micro- and nanobubbles - Seridou, Petroula; Kalogerakis, Nicolas (Environmental science. Nano, 2021)
Micro- and nanobubbles (MNBs) are microscopic gas bodies sized at micro (<100 μm) and nanoscale (<1 μm), that have a long lifetime in aqueous solutions and large specific surface area due to their small size. Recently, scientific interest has been focused on ozone micro- and nanobubbles (OMNBs) used in disinfection processes since research findings support the idea that ozone micro and nanosized bubbles can significantly improve the disinfection capacity and the residual activity of ozone. The aim of this critical review is to present recent studies which investigate the feasibility of ozone-based disinfection processes by exploiting the strong oxidizing ability of ozone and the noteworthy longevity of MNBs in aqueous solutions. Properties of MNBs and generation techniques are briefly discussed besides the monitoring methods for their characterization in terms of size and number. In this critical review, we provide recent research related to the application of OMNBs in disinfection of drinking water, as well as in aquaculture, agriculture, and wastewater treatment. Finally, research gaps and limitations of this technology are highlighted and directions for future studies are suggested. Micro- and nanobubbles (MNBs) are microscopic gas bodies sized at micro (<100 μm) and nanoscale (<1 μm), that have a long lifetime in aqueous solutions and large specific surface area due to their small size.